Ergonomics in manual lifting and load handling: A literature review on biomechanical risks and technologies for the prevention of musculoskeletal disorders (Research, Society and Development, 2026)
Work-related musculoskeletal disorders (WMSDs) represent a major occupational health problem, especially among workers exposed to manual lifting and carrying of loads. When performed under inadequate conditions of weight, posture, frequency, and work organization, these activities impose high biomechanical demands, particularly on the lumbar spine. The aim of this study was to review the scientific literature on biomechanical risks associated with manual lifting and carrying of loads, as well as ergonomic technologies and strategies applied to the prevention of musculoskeletal disorders. This is a literature review conducted using the LILACS, SciELO, Medline, and Virtual Health Library (VHL) databases, covering publications from 2019 to 2024 in Portuguese, English, and Spanish. Observational and experimental studies, as well as systematic reviews involving adult workers and outcomes related to biomechanical risk and injury prevention, were included. Of the 377 articles initially identified, 23 met the inclusion criteria. The analyzed studies indicate that manual load handling remains a significant risk factor for the development of occupational low back pain and other musculoskeletal disorders, especially when associated with trunk flexion and rotation, excessive loads, high repetitiveness, and unfavorable organizational conditions. Traditional ergonomic assessment methods, such as the Revised NIOSH Lifting Equation, proved effective in risk identification, while approaches based on wearable sensors and artificial intelligence demonstrated high potential for automated and continuous assessment. It is concluded that the integration of classical methods and emerging technologies is essential for promoting occupational health and preventing WMSDs.